Spatial model of international tourism and tourists' original motives - Oleksandr Korol; Tetiana Skutar (Kazimierz Wielki University, 2024)
Properties of geographical space essentially important for international tourism, such as length and discreteness, are analyzed. Apperception of geographical space in usual environment and its effect on tourist's original motives are described. Original motives for tourism, in particular, those of escaping, comfort, contrast and aesthetics are substantiated. Finally, upon consideration of spatial specificities of land surface and tourist-driving original motives, a conceptual model of formation and distribution of international tourism flows in geographical space is developed. The ontological-anthropologic substantiation of tarrying in usual environment and original motives for tourism has also been presented. The latter grounded on M. Heidegger's philosophy and was an attempt to understand how Human Being exists as tourist.